Comparing Home-based Pulmonary Rehabilitation Nursing on Fatigue and quality of life in Patients with COPD - Zeynab Jokar; Farahnaz Mohammadi; Hamid Reza Khankeh; Saeid Fallah Tafti; Faramarz Koushesh (Fasa University of Medical Sciences, 2014)
Background & Objective:The aim of the present study is to compare the effects of home-based pulmonary rehabilitation nursing care on Fatigue and QOL in patients with COPD. Materials & Methods: This study was a semi experimental research. The samples were consisted of 36 patients who were selected based on inclusion and exclusion criteria into control and experimental groups through random block sampling. For each of the experimental group 3 sessions of 1 hour raining over three consecutive days were done individually and it continuous up to 7 days after the patients discharged from the hospital. However, the control group was under the regular manner. Fatigue and quality of life in both groups before the intervention and 7 weeks after discharge using the Fatigue Severity Scale (FSS) and quality of life questionnaire SF-12 were compared. The data were analyzed through inferential and descriptive statistic (Independent and paired t-test, chi-square and covariance analysis). Results: Eta squared values ​​obtained in this experiment also showed that the effect of home-based pulmonary rehabilitation program on fatigue (89%) is greater than the quality of life (50%), respectively. Conclusion: As the findings indicate, the effect of home-based pulmonary rehabilitation nursing care, which has the decreasing factor on fatigue is more than the quality of life in patients with COPD.